(untitled) (Journal of Intellectual Property Rights (JIPR), 2024)
Innovation in agriculture and plant varieties is essential to serve the needs of the increasing population, maintain food security, and adhere to the principles laid down in international conventions. However, innovation in all areas including agriculture should be wary of its impact on the environment. Section 29 of the Protection of Plant Varieties and Farmers Rights Act, 2001 stipulates that a plant variety causing serious harm to the environment is incapable of registration. Nevertheless, the primary criteria for gaining registration is proof of the variety being distinct, uniform and novel. Farmers’ plant varieties lack uniformity, which paves the way for commercial breeders to gain registration. Undoubtedly, the varieties developed by commercial breeders generate higher yields. However, the same does not conform to local ecological demands and iseven less nutritious when compared to the varieties developed by the farmers. Thus, there are several consequences of permitting commercial plant varieties to take over the farmers’ plant varieties. This paper is an attempt to highlight the need for agricultural innovations to be ecologically friendly thereby, leading to a movement towards safe technology. It will also advocate for an alteration in Section 29 of the Act to make it mandatory for registration of a new plant variety.